2021
DOI: 10.3390/nu13092941
|View full text |Cite
|
Sign up to set email alerts
|

Four Weeks of 16/8 Time Restrictive Feeding in Endurance Trained Male Runners Decreases Fat Mass, without Affecting Exercise Performance

Abstract: Background: Time restricted Feeding (TRF) is a dietary pattern utilized by endurance athletes, but there is insufficient data regarding its effects on performance and metabolism in this population. The purpose of this investigation was to examine the effects of a 16/8 TRF dietary pattern on exercise performance in trained male endurance runners. Methods: A 4-week randomized crossover intervention was used to compare an 8-h TRF to a 12-h normal diet (ND) feeding window. Exercise training and dietary intake were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 56 publications
3
25
0
Order By: Relevance
“…This report extends the original findings from our TRE study in endurance-trained athletes [ 12 ] in which we observed that the TRE intervention resulted in the loss of total fat mass and body fat percentage with no change in 10 km time trial performance. In the present report, except for discovering a significant decrease in the change in segmental leg fat mass with TRE compared to normal diet, no other changes in segmental body composition, bone mineral content, resting energy expenditure, resting respiratory exchange ratio or cardiometabolic disease markers were found between the TRE and normal dietary interventions.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This report extends the original findings from our TRE study in endurance-trained athletes [ 12 ] in which we observed that the TRE intervention resulted in the loss of total fat mass and body fat percentage with no change in 10 km time trial performance. In the present report, except for discovering a significant decrease in the change in segmental leg fat mass with TRE compared to normal diet, no other changes in segmental body composition, bone mineral content, resting energy expenditure, resting respiratory exchange ratio or cardiometabolic disease markers were found between the TRE and normal dietary interventions.…”
Section: Discussionsupporting
confidence: 85%
“…We have previously reported [ 12 ] that fat mass significantly decreased by 7% and body fat percentage by 6% in the TRE group compared to no change in the ND group. These changes along with segmental body composition data are reported in ( Table 4 ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In our trial, the eTRE group lost an additional 2.3 kg relative to the control group, an approximately 50% improvement in weight loss. For comparison, prior studies are about evenly divided on whether TRE reduces body weight and are mixed for body fat, while studies that shift food intake to the morning and/or earlier in the daytime have more consistently reported weight loss . Of note, a somewhat larger study recently published in the New England Journal of Medicine by Liu et al reported that eTRE was not better for losing weight.…”
Section: Discussionmentioning
confidence: 99%